2018
DOI: 10.15252/msb.20177985
|View full text |Cite
|
Sign up to set email alerts
|

Mapping DNA damage‐dependent genetic interactions in yeast via party mating and barcode fusion genetics

Abstract: Condition‐dependent genetic interactions can reveal functional relationships between genes that are not evident under standard culture conditions. State‐of‐the‐art yeast genetic interaction mapping, which relies on robotic manipulation of arrays of double‐mutant strains, does not scale readily to multi‐condition studies. Here, we describe barcode fusion genetics to map genetic interactions (BFG‐GI), by which double‐mutant strains generated via en masse “party” mating can also be monitored en masse for growth t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 56 publications
1
21
1
Order By: Relevance
“…First, for each condition we tested, fitness estimates were highly reproducible across replicate strains carrying the same guide sequence. Previously, we, and others, have reported that when generating strains for GI screening via mating and plate-based selection, suppressors or other mutations that can affect fitness commonly occur (van Leeuwen et al 2016;Jaffe et al 2017;Díaz-Mejía et al 2018). In contrast, here, for the strains generated through pooled transformation that carry inducible gRNAs, we observed that the error on fitness across replicate strains is similar to the error across replicate cultures (Fig.…”
Section: Advantages Of Screening For Gis With Double Crispricontrasting
confidence: 38%
See 3 more Smart Citations
“…First, for each condition we tested, fitness estimates were highly reproducible across replicate strains carrying the same guide sequence. Previously, we, and others, have reported that when generating strains for GI screening via mating and plate-based selection, suppressors or other mutations that can affect fitness commonly occur (van Leeuwen et al 2016;Jaffe et al 2017;Díaz-Mejía et al 2018). In contrast, here, for the strains generated through pooled transformation that carry inducible gRNAs, we observed that the error on fitness across replicate strains is similar to the error across replicate cultures (Fig.…”
Section: Advantages Of Screening For Gis With Double Crispricontrasting
confidence: 38%
“…SGA requires that individual strains be kept spatially segregated, and as a result, large collections are impractical to store and difficult to reassay under new conditions. Pooled assays provide a potentially powerful alternative, because they require significantly less space and resources to generate, store, and subsequently assay across conditions (Pan et al 2004;Decourty et al 2008;Jaffe et al 2017;Díaz-Mejía et al 2018). Recently, we introduced a DNA barcode-fusion-based method, iSeq, to perform GI screens in a pooled format (Jaffe et al 2017).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Protein interaction networks are highly dynamic, changing in response to cellular stimuli, chemical perturbations, splice variants, or pathogenic mutations. Much of the focus of interaction proteomics has recently shifted to characterizing these changes (Sahni et al , ; Díaz‐Mejía et al , ). Consequently, any new assay should ideally detect and measure such changes.…”
Section: Schematic Representation Of Luthymentioning
confidence: 99%